2019
DOI: 10.1111/epi.16293
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of oral carbamazepine in rats dosed using an automated drug delivery system

Abstract: Objective Pharmacokinetics (PK) of antiseizure drugs differ considerably between rats and humans. Rodents require larger and more frequent doses to maintain therapeutic drug levels. This study uses the antiseizure drug (ASD) carbamazepine (CBZ) to validate the application of a previously described automated drug delivery system for delivering chronic oral medication to rats. Methods Treatment‐naive, male Sprague‐Dawley rats were treated with oral CBZ, 75 mg/kg every 6 hours for 10 days, via the automated feede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As Neuro-2a cells were exposed to CBZ, the amplitude of I Na(T) was also decreased in combination with a substantial decrease in the τ inact(S) value of the current evoked in response to the short depolarizing pulse. The previous pharmacokinetic studies have shown that following one hour of administration with CBZ, its plasma level could reach concentrations ranging between 2 and 14 μg/mL (or 8.5 and 59 μM) [ 69 , 70 ]. The observed and predicted CBZ concentrations were also found within therapeutic windows (4–12 μg/mL or 17–51 μM) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Neuro-2a cells were exposed to CBZ, the amplitude of I Na(T) was also decreased in combination with a substantial decrease in the τ inact(S) value of the current evoked in response to the short depolarizing pulse. The previous pharmacokinetic studies have shown that following one hour of administration with CBZ, its plasma level could reach concentrations ranging between 2 and 14 μg/mL (or 8.5 and 59 μM) [ 69 , 70 ]. The observed and predicted CBZ concentrations were also found within therapeutic windows (4–12 μg/mL or 17–51 μM) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous pharmacokinetic studies have shown that following one hour of administration with CBZ, its plasma level could reach concentrations ranging between 2 and 14 μg/mL (or 8.5 and 59 μM) [ 69 , 70 ]. The observed and predicted CBZ concentrations were also found within therapeutic windows (4–12 μg/mL or 17–51 μM) [ 70 ]. Moreover, the actions of CBZ on membrane excitability could be heavily dependent on various factors, including the CBZ concentration used, the pre-existing level of resting potential, different firing patterns of action potentials, and a combination of these three.…”
Section: Discussionmentioning
confidence: 99%
“…Blood levels at the end of each week were 5.5 ± 1.1, 11.5 ± 2.3, and 18.0 ± 5.3 μg/mL, respectively; n = 7 dose-response relationship and all required regular handling of the animals to administer the drugs (several times a day), which could have an impact on the seizures in addition to being stressful to the animals. One study placed the drug in the food, 16,17 but it is not clear whether this approach would work if the drug was unpalatable. These previous studies showed that using animals with higher seizure frequencies required fewer animals to show an effect.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple doses must be provided to maintain therapeutic levels while avoiding toxicity, typically by intraperitoneal or gastric gavage administration, which can be very stressful to animals and staff. Inventive approaches to chronic self‐administration have been developed, 16 but unpleasant taste may result in inconsistent levels. There are other models used for drug screening, but it is controversial whether these models really have epilepsy 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Human washed platelets were incubated with CBZ in a dose-dependent manner at 37°C for 70 H. In order to avoid lesion caused by extrusion and contamination, platelets were kept gently stirring under a sterile condition. For antiepilepsy purpose, it is the only method for CBZ to achieve the therapeutic dose range (4–12 μg/ml) in patients under steady-state conditions ( Hill et al, 2019 ). However, the peak serum concentration of CBZ can achieve more than 36 μg/ml ( Brahmi et al, 2006 ; Yang et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%